Anestesia dentária: compreendendo a percepção do cirurgião-dentista e dos pacientes - Leite, Bianca Palhano Toscano (2019)
Dental anesthesia is one of the most accomplished procedures in clinical practice. The dental fear, anxiety and stress generated by the expectation of this procedure has been the focus of many studies, which show that patients and dentists have been affected by these feelings. In order to understand the perception of dentists and patient about the clinical procedure of dental anesthesia, this study describes the data with quantitative-qualitative approach. The subjects of the research were dentists and patients who had received the dental anesthesia procedure at least once. After approval by the Research Ethics Committee, the patients were selected and the study was divided into three phases: observation, semi-structured interview with patients and dentists, and quantitative interview with patients in the waiting rooms. The analysis of the qualitative data was performed based on the content analysis of Bardin (2011) and the descriptive statistics of the quantitative data were performed with the variables compared by the exact Fisher, Pearson or Wilcoxon chi-square tests. Most patients reported no pain in dental procedures, despite the distinct dental anxiety. The value found by the visual analogue scale to measure pain in anesthesia was 2.26. Dentists generally feel safe and quiet when applying anesthesia, except in anxious patients, and in addition, find the profession stressful. With a better understanding of dental anesthesia and the feelings involved in it, dentists can use appropriate techniques to improve patients' comfort, fear and anxiety and thereby reduce levels of pain and stress.